Assessing The Potential Of Indigenous Bacillus cereus For Soil Crack Healing Via Microbiologically Induced Calcium Carbonate Precipitation - Mustafa, Muskhazli; Huzairi, Luqman Hakeem; Abdul Aziz, Nor AzwadyAbdul Aziz; Fadzel, Nini Tasnim; Mohamed Ghazali, Mona Fatin Syazwanee; Go, Rusea (Malaysian Applied Biology, 2026)
The utilisation of indigenous ureolytic bacteria for the rehabilitation of soil slope cracks through microbial-induced calcite precipitation (MICP) is cost-effective and eco-friendly. This study was designed to assess the soil's crack-healing potential of the indigenous bacteria, Bacillus cereus. A solution containing the urease-producing B. cereus and B. megaterium (control treatment) and a cementation solution was sprayed onto the cracks; this process was repeated five times. B. cereus treatment induced soil crack repair, with an average reduction in width of 0.20 ± 0.113 mm from the initial width of 0.45 ± 0.187 mm, but the decrease in cracks was not significantly different compared to that observed for B. megaterium. Soil treated with B. cereus contained significantly more CaCO3 per 20 g of soil (0.78 ± 0.102 g vs. 0.59 ± 0.220 g) compared to B. megaterium and provided optimal growth conditions for the native B. cereus. However, X-ray diffraction analysis revealed that only 1.5% of the precipitated CaCO3 was in the form of calcite, while aragonite constituted 28.5% and vaterite accounted for 70% of the different crystal structures. B. megaterium was composed of 46% calcite, 24.5% aragonite, and 29.5% vaterite crystals. These findings indicate a positive outlook for the use of indigenous microbial-induced calcite precipitation, especially for fracture repair. Further research is required to determine the mechanism underlying the calcification process of native bacteria and the specific conditions necessary to initiate the formation of calcium carbonate biominerals.